Pulse-Width Modulation Template for Five-Level Switch-Clamped H-Bridge-Based Cascaded Multilevel Inverter - Charles Ikechukwu Odeh (MDPI AG, 2021)
This article presents a carrier-based pulse-width modulation (PWM) template for a 5-level, H bridge-based cascaded multilevel inverter (MLI). The developed control concept generates adequate modulation template for this inverter topology wherein a sinusoidal modulating waveform is modified to fit in a single triangular carrier signal range. With this modulation approach, classical multiplicity and synchronization of the triangular carrier signals criterion for the extension of sinusoidal pulse-width modulation, SPWM, to several cascaded 5-level, H-bridge-based MLI topology are removed. The proposed template can be used on the inverter configuration of any level with no further control modification. Nearly even distribution of switching pulses and equalized individual cascaded cell output power were achieved with the proposed modulation scheme. Three 5-level, H-bridge-based MLI units were cascaded for 1-phase, 13-level inverter operation; simulation and experimental results are adequately presented.